2020
DOI: 10.1364/ao.402704
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a micro-lens array for improving depth-of-field of integral imaging 3D display

Abstract: In this paper, we present a new, to the best of our knowledge, structure of double pinhole/micro-lens array (DP/MLA) with two center-depth planes, used for improving the depth-of-field (DOF) of integral imaging (II), which can be fabricated by a combination of lithography and inkjet printing. The results show that a black circular groove array prepared by lithography can be used for micro-lens location and reduce the stray light for II. By controlling the parameters of the inkjet printing system, DP/MLA with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…It can be seen that the focal length and f-number decreased from 55.59 to 9.34 µm and from 2.78 to 0.95, respectively, while the NA of MLAs was controllable increasing from 0.18 to 0.53 through different PDMS nanofilm modified substrates. The calculated f-number is 0.95 for the microlens on the T4 substrate, which is 13.6% smaller than the minimum value in previous studies using other methods, [2,42,44,45,46] as shown in Table S1 (Supporting Information). The smaller f-number indicates the enhanced light-gathering power of the MLAs with the increased resolutions of geometrical properties (smaller diameter and larger height) due to the PDMS nanofilm modification.…”
Section: Effects Of Contact Angle On the Diameter And Na Of Mlascontrasting
confidence: 63%
See 2 more Smart Citations
“…It can be seen that the focal length and f-number decreased from 55.59 to 9.34 µm and from 2.78 to 0.95, respectively, while the NA of MLAs was controllable increasing from 0.18 to 0.53 through different PDMS nanofilm modified substrates. The calculated f-number is 0.95 for the microlens on the T4 substrate, which is 13.6% smaller than the minimum value in previous studies using other methods, [2,42,44,45,46] as shown in Table S1 (Supporting Information). The smaller f-number indicates the enhanced light-gathering power of the MLAs with the increased resolutions of geometrical properties (smaller diameter and larger height) due to the PDMS nanofilm modification.…”
Section: Effects Of Contact Angle On the Diameter And Na Of Mlascontrasting
confidence: 63%
“…In recent years, microlens arrays (MLAs) have attracted extensive attention due to their wide applications in various fields such as digital displays, [ 1–3 ] light‐emitting‐diodes (LEDs), [ 4,5,6,7 ] super‐resolution imaging, [ 8,9,10 ] and artificial compound eyes. [ 11,12,13 ] The demand of MLAs with precise shaping features has increased over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each CDP can display the image of the corresponding focal length. The distance between the two CDPs is: [134]…”
Section: Enhancement Of Depth Of Fieldmentioning
confidence: 99%
“…where b1 and b2 are the distances from lens array 1 to the central depth plane 1 and 2, respectively; d is the distance between the two lens arrays; a is the distance from the display screen to lens array 2; and f is the refractive index of the lens array. [134] Duallayer lens array with a complementary symmetrical structure can increase the number of CDP by increasing the number of layers of the lens array, to realize the function of increasing the DOF. Nanotarget.…”
Section: Enhancement Of Depth Of Fieldmentioning
confidence: 99%